Training According To Pro-Split System And Its Effect On Some Biochemical Indicators, Maximum Strength, And Clean And Jerk Performance For Advanced Weightlifters - Wissam Yasseen Burhan; Majid Abdul Hameed Rasheed, (Musamus Journal of Physical Education and Sport (MJPES), 2026)
This study aimed to identify the changes caused by Pro-Split training in certain biochemical indicators, maximum strength, and clean and jerk performance among advanced weightlifters. The researchers employed an experimental design with two equivalent groups using pre- and post-testing. The study population consisted of ten advanced weightlifters from Al-Rafidain Sports Club. After ensuring homogeneity and equivalence of variables to eliminate any external influence on the independent variable, the participants were divided into two groups: a control group and an experimental group of five weightlifters each. The researchers then implemented the Pro-Split training system to observe its effects on biochemical indicators, maximum strength, and clean and jerk performance. The training program lasted eight weeks, with three training sessions per week. The most significant finding was that Pro-Split training targeted the muscles from all angles and aspects, thereby enhancing coordination and synergy among the muscles involved in the exercise.The study concluded that Pro-Split training targeted the muscles from all angles and aspects, leading to improved coordination and synergy among the muscles involved in the exercise.